2013
DOI: 10.1007/s10120-013-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Petersen’s hernia after laparoscopic distal gastrectomy with Roux-en-Y reconstruction for gastric cancer

Abstract: Background To decrease the incidence of internal hernia after laparoscopic Roux-en-Y gastric bypass, recent recommendations indicated closure of mesenteric defects and Petersen's defect. Laparoscopic distal gastrectomy for gastric cancer is used increasingly, so the incidence of Petersen's hernia can also increase, but the trend has not been studied. Methods This study retrospectively reviewed 358 consecutive patients who underwent laparoscopic distal gastrectomy for gastric cancer at one institution, with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…To minimize the occurrence of internal hernia, closure of the jejunojejunal mesenteric defect and Petersen's defect with continuous nonabsorbable sutures is recommended when performing laparoscopic distal gastrectomy and R-Y reconstruction, which is consistent with the recommendations for laparoscopic RYGBP with antecolic R-Y reconstruction [9]. Weight loss after esophagectomy was 9.3 % of preoperative body weight.…”
Section: Discussionmentioning
confidence: 56%
“…To minimize the occurrence of internal hernia, closure of the jejunojejunal mesenteric defect and Petersen's defect with continuous nonabsorbable sutures is recommended when performing laparoscopic distal gastrectomy and R-Y reconstruction, which is consistent with the recommendations for laparoscopic RYGBP with antecolic R-Y reconstruction [9]. Weight loss after esophagectomy was 9.3 % of preoperative body weight.…”
Section: Discussionmentioning
confidence: 56%
“…Some studies have demonstrated lower occurrence of internal hernia after a switch in practice by closing the defects (table 2). 1 2 4 A large Japanese study revealed a significant reduction in incidence of internal hernia (jejunojejunostomy mesenteric defect; 0% vs 3.4%, p=0.01) and a similar trend in Petersen's defect 2. In Miyagaki et al 's series,6 they do not close Petersen's space and opinioned that if the orifice is not closed, it should be left large to allow transposition of small bowel and avoid incarceration.…”
Section: Discussionmentioning
confidence: 98%
“…Following Roux-en-Y reconstruction, Petersen's spaces, jejuna-jejunal spaces, and transverse mesocolon spaces (if anastomosis was performed retrocolic) was formed. The herniation of intestinal structures through such spaces may lead to intestinal obstruction, ischemia, or necrosis (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this situation include the decrease in mesenteric fat tissue because of postoperative weight loss, lesser amount of adhesions following laparoscopic surgery, leaving a longer Roux limb, and the . Internal herniation after laparoscopic gastric resection can be seen at any time after surgery, but the prevalence increases after the first year (1,4,5). In a study by Kelly et al (3), the authors stated that the rate of internal herniation following laparoscopic total gastrectomy was 22% at the end of an average of 22.4-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation